"Verumtamen Non Sicut Ego Volo Sed Sicut Tu": Análisis y traducción de Ordinatio III, d. 17, q. unica de Juan Duns Escoto - Rodríguez Morales, Jesús Manuel (Miscellanea francescana, 2024)
The contribution examines the implications of the concept of will beginning with distinction 17 of Duns Scotus' commentary on the third book of the Sentences by Peter Lombard on the double will in Christ. In this passage, the Franciscan Master establishes a clear distinction between the voluntas libera and the voluntas naturalis which gives space to a renewed reading of the primacy of the will, of which the autonomy and freedom in the face of the decrees of nature and reason are highlighted. Consequently, the answer to the Christological question leads Duns Scotus to support, in line with John of Damascus, the coexistence of the dual nature and will of Christ. From this conclusion, a clear distinction can be drawn between the positions of Duns Scotus and those of Aristotle, to the extent that the primacy of the will of the former transcends the conceptual determinism of nature and human forms of the latter. The article provides the reader with the full translation into Spanish of the Scotist question.